2015
DOI: 10.14639/0392-100x-669
|View full text |Cite
|
Sign up to set email alerts
|

Predittori di efficacia nel trattamento dell'otite esterna maligna fungina: una review sistematica

Abstract: Obiettivo dello studio è stato riassumere i dati della letteratura sugli aspetti clinici e la gestione abituale dell’otite esterna maligna fungina (OEMF), ed identificare possibili fattori predittivi di esito positivo del trattamento. Gli articoli sono stati inizialmente selezionati sulla base del titolo e degli abstract. Sono poi stati recuperati ed analizzati per intero seguendo criteri predeterminati. È stata stilata una lista di riferimento degli articoli selezionati per cercare eventuali pubblicazioni man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
2
7
3
1
Order By: Relevance
“…The increased rate of facial nerve palsy seen in fungal TBO may be attributable to a delay in diagnosis with resultant progression of disease or be indicative of a more extensive disease pattern. A high proportion of those without facial nerve palsy recovered from fungal TBO, which is consistent with previous findings (10).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The increased rate of facial nerve palsy seen in fungal TBO may be attributable to a delay in diagnosis with resultant progression of disease or be indicative of a more extensive disease pattern. A high proportion of those without facial nerve palsy recovered from fungal TBO, which is consistent with previous findings (10).…”
Section: Discussionsupporting
confidence: 92%
“…The decision to surgically intervene in patients with fungal TBO can present a therapeutic challenge. Although a previous review found an association between no surgical intervention and symptom resolution in fungal TBO (10), we found a majority of patients who underwent surgery ultimately recovered. The general trend has moved away from surgical intervention in TBO in the last few decades, yet there has been a resurgence of performing surgery in advanced or aggressive cases (9,99).…”
Section: Treatment Strategiescontrasting
confidence: 92%
See 3 more Smart Citations